2014
DOI: 10.1055/s-0034-1384543
|View full text |Cite
|
Sign up to set email alerts
|

Instrument-assisted Soft Tissue Mobilization: Effects on the Properties of Human Plantar Flexors

Abstract: • ▶ muscle-tendon stiff ness • ▶ infl ammatory response • ▶ injury • ▶ therapeutic modality Instrument-assisted Soft Tissue Mobilization: Eff ects on the Properties of Human Plantar Flexorstion following eccentric exercise may be important components for the recovery of muscle tissue [ 20 ] . Though this research provides the most recent mechanistic example of the response to soft tissue mobilization in an animal model, the physiological diff erences to that of human subjects may limit its clinical applicabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
62
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(75 citation statements)
references
References 42 publications
9
62
2
2
Order By: Relevance
“…However, there is compelling evidence that pre-exercise static stretching could also impair neuromuscular performance (Behm and Chaouachi, 2011;Simic et al, 2013). Aside from stretching, self-myofascial release with foam roller (FR) or stick roller (SR) (Button et al, 2015;Halperin et al, 2014;MacDonald et al, 2013;Mohr et al, 2014;Sullivan et al, 2013), and instrument assisted soft-tissue mobilization (IASTM;Laudner et al, 2014;Vardiman et al, 2015) have been recently used in clinical and sports practice for joint ROM enhancement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is compelling evidence that pre-exercise static stretching could also impair neuromuscular performance (Behm and Chaouachi, 2011;Simic et al, 2013). Aside from stretching, self-myofascial release with foam roller (FR) or stick roller (SR) (Button et al, 2015;Halperin et al, 2014;MacDonald et al, 2013;Mohr et al, 2014;Sullivan et al, 2013), and instrument assisted soft-tissue mobilization (IASTM;Laudner et al, 2014;Vardiman et al, 2015) have been recently used in clinical and sports practice for joint ROM enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding IASTM, limited previous studies provided conflicting findings (Laudner et al, 2014;Vardiman et al, 2015). Laudner et al (2014) showed that the application a Graston technique (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…TheAcupunctureVol.34No.3August2017 lief and increased ROM. The Iastm, Graston, and Astym techniques are widely used 23) .…”
Section: Instrument-assisted Soft Tissue Mobilizationmentioning
confidence: 99%
“…19 The purpose of this study was to examine the effect of Astym treatment on ADL of women who had undergone a mastectomy following a diagnosis of breast cancer. The specific aims of the study were to examine differences in 1) a patient's subjective assessment of functional disability through the DASH score, 2) the ability to wear a bra through a clothing questionnaire, 3) up to five functional activities women have reported to be difficult after mastectomy using the Patient-Specific Functional Scale (PSFS), 4) shoulder flexion, and 5) shoulder abduction, before and after a course of Astym therapy.…”
Section: Astymmentioning
confidence: 99%